Pengaruh Gaya Hidup, Inovasi Produk dan Daya Tarik Iklan Terhadap Keputusan Pembelian pada Konsumen di Umama Gallery Surabaya - Rahmawati, Cindy Sekar; Mulyati, Awin; Mulyati, Diana Juni (Jurnal Dinamika Administrasi Bisnis, 2021)
ABSTRACT            Currently the trend is  hijabvery prevalent among adolescents to adults. As a business owner in the hijab world, it is necessary to pay attention to lifestyle, product innovation and the attractiveness of advertising for the development of its business in the future. Because increased lifestyles will affect consumer behavior, so product innovation and ad appeal need to be considered and always maintained.             This study aims to determine the effect of lifestyle, product innovation and the attractiveness of advertisements on purchasing decisions on consumers at Umama Gallery Surabaya. The population used in this study were all women who used the Umama Scarf hijab. The sample used amounted to 100 respondents who at that time met coincidentally with the researcher and could be used as a sample because it was considered suitable with the data source or could be referred to by using accidental sampling technique. Data was collected through questionnaires distributed to respondents. Analysis of data using validity test, reliability test, test multiple linear regression analysis, correlation (r), test the coefficient of determination (R2),simultaneous test (F test) and t test (partial). All data analyzes were performed with the help of IBM SPSS Statistics Version 21.             The results showed that there was a positive and significant influence between lifestyle on purchasing decisions, there was a positive and significant influence between product innovation on purchasing decisions, there was a positive and significant effect between the attractiveness of advertising on purchasing decisions, lifestyle, product innovation and attractiveness of advertising jointly influence on purchasing decisions and product innovation has the most dominant influence on purchasing decisions on consumers at Umama Gallery Surabaya. Therefore, companies need to maintain product innovation that have been made and it is necessary to increase product innovation by producing hijab are not owned by brand Umamaso that consumers feel the hijab scarf Scarf Umama always be able to meet the needs of consumers and consumer purchasing decisions can also be increased.Keywords: Lifestyle, Product Innovation, Attractiveness of Advertising, Purchasing Decisions